2018
DOI: 10.1039/c8an00881g
|View full text |Cite
|
Sign up to set email alerts
|

Small volume method for drug release screening using ultrasonic agitation

Abstract: Ultrasound delivered via a microprobe horn allows for tunable and repeatable screening of drug release behavior in small volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…26 Drug Release from Neat Naproxen and Naproxen− Ethyl Cellulose Particles. We conducted small-volume in vitro drug release studies using a protocol developed by Acevedo et al, 20 on the neat naproxen and naproxen−ethyl cellulose microparticles to evaluate the extent to which different particle structures affect drug release. PXRD analysis was first conducted to verify the naproxen polymorph within the microparticles prior to drug release testing.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Drug Release from Neat Naproxen and Naproxen− Ethyl Cellulose Particles. We conducted small-volume in vitro drug release studies using a protocol developed by Acevedo et al, 20 on the neat naproxen and naproxen−ethyl cellulose microparticles to evaluate the extent to which different particle structures affect drug release. PXRD analysis was first conducted to verify the naproxen polymorph within the microparticles prior to drug release testing.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…All collected particles were collected on filter paper, rinsed thrice with ultrapure water to remove traces of surfactant, and vacuum-dried at room temperature for 8 h prior to structural and polymorphic characterization. Drug-release studies from neat naproxen and naproxen− ethyl cellulose particles made using the protocol described above were conducted using the small-volume method described by Acevedo et al 20 A phosphate-buffered saline (PBS) stock solution was prepared by dissolving a 5 g Gibco PBS tablet into 500 mL of ultrapure water, and the test media used for all samples was 50 mL of the PBS solution. The mass of each particle type used per test was set such that the expected amount of naproxen was ∼2.5 mg. A 60 mL roundbottom, plastic test tube (BRAND, Sigma-Aldrich) was used as the test vessel.…”
Section: ■ Introductionmentioning
confidence: 99%
“…48 In collaboration with an acoustics expert in the Mechanical Engineering department at Boston University, we showed that drug release kinetics could be tuned by varying input power and distance from the acoustic source to the dissolving tablet. 49 The guiding questions related to the "Assay" processes include:…”
Section: Second Prototype With Automated Sample Preparation (2015-2018)mentioning
confidence: 99%
“…The development of affordable devices (in terms of time/resources consumed and user skills required) for dissolution testing is in its infancy. Research to investigate devices for quantification of drug release to probe differences in dosage form composition are underway [ 32 , 33 ].…”
Section: The Need For More Evidencementioning
confidence: 99%